PENERAPAN MODEL TEMATIK MENGGUNKAN MICROSOF POWER POINT DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP - Prasandi, Robby Anggara; Khosmas, F.Y.; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to find out the effectiveness of the implementation of tematic learning by using Microsoft Powerpoint to improve student? learning outcomes of Social Science on the Grade VII of SMP Negeri 8 Pontianak. The method used was Quasi Experimental Design that planned with Nonequivalent Control Group Design. There were 56 students in this research. This research variabke were independent and dependent variables. Tematic model and Microsoft Powerpoint were the independent variables while the students achievement was the dependent one. The data analysis result showed  that there was a significant difference on student learning outcomes betweem experimental class and controll class. It was proven in control class that carried with coventional learning method gained 77,5 average score in post test. While in experimental class that carried with tematic learning by using Microsoft Powerpoint gained 89,8 that means there was an improvement. This was directly proportional with the effect size  gained that was 2,66 which means the achievement was high clasified. Keywords: Tematik  Model, The Microsoft Power Point, Learning Outcomes.